Synthesis and photocatalytic properties of bismuth titanate with different structures via oxidant peroxo method (OPM) - Nogueira, Andre E.; Longo, Elson [UNESP]; Leite, Edson R.; Camargo, Emerson R. (Elsevier B.V., 2014)
Bismuth titanate (Bi4Ti3O12 and Bi12TiO20) Powders were synthesized by the Oxidant Peroxide Method (OPM), and the effect of temperatures on physical and chemical properties of particles was investigated. The results showed that the morphology and average particle size of materials can be successfully controlled by adjusting the temperature. The samples after calcination were characterized by X-ray diffractometry, transmission electron microscopy, diffuse reflectance spectroscopy, Raman spectroscopy, and BET isotherms. The photocatalytic activity of materials was also evaluated by studying the degradation of 10 ppm aqueous rhodamine B dye under ultraviolet radiation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bismuth titanate; Photocatalyst; OPM route